Communication physical, mechanical, thermal and acoustic properties of processing and cutting materials in machining. - Буряк, А.В.; Буряк, В.Г. (Problems of Tribology, 2016)
Buryak A.V., Buryak V.G. Communication physical, mechanical, thermal and acoustic properties of process-ing and cutting materials in machining. The connection of the physical and mechanical, thermal and acoustic properties of machining and tool materials, which determine the performance of cutting tools. The attention given to the wear resistance of tools, which enables to increase the processing performance and is an important condition for automated manufacturing. Keywords: machining, physical, mechanical, thermal and acoustic properties of the material causal link wear.